When Coordinating Finger Tapping to a Variable Beat the Variability Scaling Structure of the Movement and the Cortical BOLD Signal are Both Entrained to the Auditory Stimuli. (10th November 2018) - Harrison, Steven J.; Hough, Michael; Schmid, Kendra; Groff, Boman R.; Stergiou, Nicholas
Highlights: Measures of brain and behavior often possess specific variability scaling properties (i.e. statistical self-similarity). We show the variability scalings of auditory stimuli, motor behavior, and cortical hemodynamics to be interdependent. Changes in variability scaling of auditory stimuli produce matching changes in motor variability scaling. Changes in variability scaling of auditory stimuli produce matching directional shifts in HbO2 signal variability scaling. These matchings suggest that auditory stimuli engage both brain and behavior at the level of variability scaling structures. Abstract: Rhythmic actions are characterizable as a repeating invariant pattern of movement together with variability taking the form of cycle-to-cycle fluctuations. Variability in behavioral measures is atypically random, and often exhibits serial temporal dependencies and statistical self-similarity in the scaling of variability magnitudes across timescales. Self-similar (i.e. fractal) variability scaling is evident in measures of both brain and behavior. Variability scaling structure can be quantified via the scaling exponent ( α ) from detrended fluctuation analysis (DFA). Here we study the task of coordinating thumb-finger tapping to the beats of constructed auditory stimuli. We test the hypothesis that variability scaling evident in tap-to-tap intervals as well as in the fluctuations of cortical hemodynamics will become entrained to (i.e. drawn toward) manipulated changes in the variability scaling of a stimulus's beat-to-beat intervals. Consistent with this hypothesis, manipulated changes of the exponent α of the experimental stimuli produced corresponding changes in the exponent α of both tap-to-tap intervals and cortical hemodynamics. The changes in hemodynamics were observed in both motor and sensorimotor cortical areas in the contralateral hemisphere. These results were observed only for the longer timescales of the detrended fluctuation analysis used to measure the exponent α . These findings suggest that complex auditory stimuli engage both brain and behavior at the level of variability scaling structures.